Creating a High-Performance Workplace: The Contribution of Work Discipline and Physical Environment - Nadzir , Muhammad Ihsan; Poerwita Sary, Fetty (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Firms competing in dynamic environments must strategically align human resource practices to sustain performance. This study advances theory by integrating physical workplace conditions and behavioral discipline within a unified structural model, clarifying their relative predictive strength on employee performance in service organizations. Using a quantitative, descriptive–causal design, data were collected from 222 employees through a saturated sampling approach and analyzed with PLS-SEM. The results reveal that both physical work environment and work discipline significantly enhance performance, with discipline exerting the stronger effect. These findings refine human resource management literature by demonstrating that behavioral regulation mechanisms may outweigh contextual physical factors in shaping performance outcomes. Practically, organizations should prioritize disciplined work systems while maintaining supportive physical conditions to optimize employee productivity and organizational effectiveness.